Does Financial Literacy Affect the Use of Cashless Payment among Gen Z in Medan City - Dewi Rafiah Pakpahan (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to determine whether financial literacy affects the use of non-cash payments for Gen Z in Medan City. This study uses a quantitative research approach to analyze and describe the influence between independent variables consisting of Finncial Literacy (FL), Performance Expectancy (PE), and Social Influence (SI) and using intention to use non-cash payments (BI) as an independent variable. The population of this research is Gen Z in Medan City. Gen Z was chosen as the respondent because they are considered to have complex financial knowledge ranging from basic to advanced levels. this study analyzed the relationship between variables using the Partial Least Square (PLS) analysis model. The results of this study are Directly shows that financial literacy has a positive effect on the intention to use non-cash payments. Performance Expectancy directly has a positive effect on the intention to use non-cash payments, and social influence has a positive effect on the intention to use non-cash payments. Suggestions to non-cash service providers to be able to use a variety of different communication communication tools to create usage trends or hire influential figures to promote their products or services to attract consumers to use non-cash payment systems.